A universalidade da educação em Hegel - Novelli, Pedro Geraldo Aparecido [UNESP] (My University, 2012)
Cannot the education reach the universality? Is the universality the annihilation of the individual? Can the individual have his identity preserved as such in the State? Those questions are answered with the attention returned and led to the education. To Hegel the education universalizes the individual insofar as it introduces him into the life of the State in which the subjectivity and individuality are known in fact, preserved and promoted. In the Elements of the Philosophy of Right, Hegel deals with the realization of freedom in the institution of State and identifies it with the realization of freedom. The aim here is to reflect upon the Hegelian comprehension of State towards education, its meaning, signification to the life of the State and its possible repercussions regarding the figures of the subject and individual also nowadays. To Hegel the education supports the State as such because it is the process of the Sate’s awareness along its formation as a living organism. A State that knows itself is a State that is known by its members who do not reach neither the State’s awareness nor themselves’ without the relation that gathers them together as the substantial universality. The education is the means that brings the individuals to the life of the State. Bringing the individual to the life in the State, the education reveals the individual to himself as well as to his true nature, that is, a being in relation to others who are not but himself. The knowledge of oneself in the education happens also through its formalization regarding the specific contents developed and accumulated throughout the history. Here comes the figure of the formal educator through whom the State aims its process of formation. This way Hegel confirms that nobody learns alone and that the universal is precisely this relation.

Pode a educacao nao ter o alcance da universalidade? A universalidade é o aniquilamento do indivíduo? Pode o indivíduo ter sua indentidade enquanto tal preservada no Estado? Essas questoes sao respondidas com a atencao retomada e dirigda à educacao. Para Hegel a educacao universaliza o indivíduo na medida em que o introduz na vida do Estado no qual a subjetividade e a individualidade sao de fato conhecidas, preservadas e promovidas. Nos Princípios da Filosofia do Direito Hegel se ocupa com a realizacao da liberdade na instituicao do Estado e identifica o mesmo com a realizacao da liberdade. O objetivo aqui é refletir à luz da compreensao hegeliana de Estado sobre a educacao, seu significado, sua significacao para a vida do Estado e suas possíveis repercussoes sobre as figuras do sujeito e do indivíduo também na atualidade. Para Hegel a educacao sustenta o Estado enquanto tal, pois é o processo de conscientizacao do mesmo ao longo de sua formacao enquanto organismo vivo. Um Estado sabedor de si é um Estado que é sabido pelos seus membros. Estes nao chegam à consciência do Estado ou de si mesmos sem a relacao que os congrega enquanto universalidade substancial. A educacao é a mediacao pela qual o indivíduo é trazido à vida do Estado. Ao trazer o indivíduo à vida no Estado a educacao revela o indivíduo para si mesmo e revela também sua verdadeira natureza, ou seja, ser em relacao com outros que nao sao senao ele mesmo. O conhecimento de si na educacao se dá também pela formalizacao da mesma nos conteúdos específicos desenvolvidos e acumulados ao longo da história. Aqui entra a figura do educador formal pelo qual o Estado objetiva seu processo de formacao. Desse modo confirma Hegel que ninguém aprende sozinho e que o universal é precisamente essa relacao.
Keywords: Dialética; Educação; Sociedade